Optimization of biodiesel production from rice bran oil by ultrasound and infrared radiation using ANN-GWO. (15th August 2023) - Sebayang, A.H.; Kusumo, Fitranto; Milano, Jassinnee; Shamsuddin, A.H.; Silitonga, A.S.; Ideris, F.; Siswantoro, Joko; Veza, Ibham; Mofijur, M.; Reen Chia, Shir
Graphical abstract: Highlights: Rice bran biodiesel is produced using ultrasound and infrared radiation. ANN-GWO is a reliable tool to optimize the transesterification process. The predicted rice bran yield is 98.16%. The optimum yield obtained from the experiment is 97.74%. The FAME content of the optimized biodiesel is 95%. Abstract: A system combining ultrasound and infrared radiation was used to increase the chemical reactions between incompressible reactants by enhancing their mass transfers with the aim to reduce the energy usage and reaction time. In this study, biodiesel from RBO was produced via transesterification, and the process variables were optimized using the combination of ANN and GWO algorithm. Process parameters considered in this study are ratio of methanol to oil, catalyst concentration, and reaction time. Based on the ANN-GWO algoritm used, the optimum conditions for the process parameters were (1) methanol to oil ratio: 60%, (2) concentration of catalyst: 1 wt%, (3) time: 7.76 min, leading to the metyl ester yield of 98.16 wt%. The algoritm was verified by conducting a triplicate independent experiments using the suggested optimum values, resulting in an average methyl ester yield of 97.74 wt%. Subsequently, properties of rice bran biodiesel were compared to ASTM D6751 and EN 14214 standards, and the obtained values met both the standards.